UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN SEDERHANA MELALUI MEDIA KARTU PECAHAN DI KELAS III UPT SD NEGERI 20 BARINGIN - Arbaidah Arbaidah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This study aims to improve the mathematics learning outcomes of class III UPT students. SD Negeri 20 Baringin through the media of fractional cards. This study used a classroom action research design with the Kemmis & McTaggart model. The research subjects were students of class III UPT. SD Negeri 20 Baringin, totaling 35 students, consists of 20 male students and 15 female students. The object of this research is the result of learning mathematics in simple fractions material after using fraction card media. The data collection instruments used observation sheets and tests. The data analysis technique used is descriptive quantitative analysis and qualitative descriptive analysis. The success of this research is that at least 85% of the total number of students reaches the Minimum Completion Criteria (KKM) that has been set by the school, namely 80 and the percentage of teacher and student activities obtained reaches 75% with good classification. The results showed that the use of fraction card media could improve mathematics learning outcomes comparing simple fractions of class III UPT students. SD Negeri 20 Baringin. The results of observations in cycles I and II showed an increase in student activity in learning using fraction card media from 66.7% to 84.9% and teacher activity increased from 72% to 82.5%. The increase in the percentage of students who achieved the KKM score in cycle I and cycle II was 22.9%, from 23 students (65.7%) to 31 students (88.6%). The average learning outcomes in cycle I to cycle II increased from 76 to 84.